Human glioma proliferative potential investigation in the short-term culture for determination to anablastic chemopreparations sensitivity - Vasilyeva, I. G.; Rozumenko, V. D.; Glavatsky, A. Ya.; Olexenko, N. P.; Galanta, E. S.; Chopik, N. G.; Tsyubko, O. I.; Vaschulenko, T. N. (Ukrainian Neurosurgical Journal, 2005)
Н3-thymydine accumulation was investigated in the short-term cultures, which were obtained from 20 samples of human brain gliomas. It was confirmed that tumors with accumulation did not differ from the phone level in all histological groups. In other samples the level of labled nucleothyde was very different inside the histological groups. The conditions in wich radioactivity level changed that demonstrated the personal tumor's cells drug sensitivity were discussed.